A comparative analysis on six switch inverter and four switch inverter fed three phase induction motor - Vijayan, Gopika; V.P, Vinod; T, Sreejith (International Journal of Engineering and Technology, 2018)
In small scale applications where the Induction motors are powered from dc supply, the inverter assumes an imperative part in changing over the dc voltage to the required ac voltage. This paper manages the correlation of three phase six switch inverter and three phase four switch inverter. Each voltage source inverter requires PWM system for their activity. Space vector pulse width modulation (SVPWM) pro-cedure was utilized as a part of this work for setting off the inverter. This work is persuaded by the need of inverter with decreased segment cost and high effectiveness. Both the inverters were displayed in MATLAB Simulink and the outcomes were observedÂ Â